Propose Development of the Features and Benefits of BTN Prima iB Savings. Case Study : PT.Bank Tabungan Negara Sharia Business Unit - Tri Endharto, Nadia; B.Saksono, Prasetyo (The Indonesian Journal of Business Administration, 2016)
Abstract. This final project aims to determine what is the causes of lower achievement of BTN Prima iB savings target on BTN Syariah and also seek for customer needs of the product offered related features and benefits. This research deploys 215 questionnaires to existing customer in BTN Syariah. Then, by using SPSS, calculation data result provide correlation analysis to see the relationship between features and benefits of BTN Prima iB savings to increase achievement of sales target. Based on the analysis, it was found that existing features and benefits of BTN Prima iB savings are less interested by customer. These mainly related with three aspects; technology, regulation, and customersâ€™ privilege. So, this study will provide proposal to develop new features and benefits of savings BTN Prima iB in order to increase the target achievement of BTN Prima iB savings.Â Key words: BTN Prima iB savings, Islamic Banking, Development Features and Benefit, Correlation Analysis